Autekologi Impatiens mamasensis Utami & Wiriad. di Kawasan Resort Tongoa Taman Nasional Lore Lindu Sulawesi Tengah - Dian Moh Fauzan; Ramadhanil Pitopang; Samsurizal Suleman (Biocelebes, 2018)
A research entitled “Autecological study of Impatiens mamasensis Utami & Wiriad. In the Tongoa resort of Lore Lindu National Park Central Sulawesi has been carried out from April to May 2016. The research objectives was to describe the environmental factor of habitat of I. mamasensis Utami & Wiriad including abiotic and biotic factor. The abiotic factors which was observed such temperature and humidity were measured by Termohygrometer, light intensity by lux meter, and  soil pH and soil humidity were calculated by Soil tester. Geographical position measured by Global Positioning System/ GPS). Meanwhile, rainfall data obtained from the Meteorological and Geophysics Palu. Concentrations of Nitrogen, of habitat was analyzed by the Kjehdahl method whereas Phosphorus, and Potassium was analyzed by extracting 25% HCL. Vegetation was analyzed by using double plot method with plot size 2 by 2 m in size. The results showed that  I. mamasensis grew well at an altitude of 1500 to 1700 m asl with daily temperatures ranged from 17.3 to 23.8 ° C, relative humidity varied from 68.5 to 83.7% soil pH  from 5,8 to 7 and soil humidity ranges from 50 to 80%.  Rainfall was 448 mm and 205 during  April to May. I. mamasensis grow in low concentration N meanwhile concentration P and K soil with moderate concentration. The vegetation is dominated by Elatostema strigosum (Bl.) Hassk (IVI 14,81%.), Desmodium repandum (Vahl.) DC. (IVI 9,71%), Crypsinus montanus Sledge sp (IVI 9,56%), Geophila repens (L.) I.M. Johnst. (INP 9,29%). I noted a number species of  insects ie, Tetrigidae, Tachinidae,  Aulacophora sp, Chrysosoma sp, and Episyrpus sp. The results of this study are expected to provide useful information for the benefit of ex-situ conservation acclimation and cultivation research Impatiens mamasensis Utami & Wiriad. in order to prevent this endemic species from extinction.Key words:  Autecology, Impatiens mamasensis Utami & Wiriad., Lore Lindu National Park (LLNP)..